2022
DOI: 10.1002/ptr.7612
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fenugreek seed extract supplementation in patients with Alzheimer's disease: A randomized, double‐blind, placebo‐controlled trial

Abstract: The aim of the current randomized control trial (RCT) study was to investigate the effects of fenugreek seed extract on memory, depression, quality of life, blood pressure, and serum malondialdehyde (MDA) and total antioxidant capacity (TAC) levels in adult AD patients. This randomized clinical trial was conducted in geriatric homes in Iran. The study participants included 82 AD patients with mild‐to‐moderate memory deficit. Patients in the intervention group received 5 cc of fenugreek seed extract for 4 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In our current summary research, in a study by Thaung Zaw JJ et al [80], a daily supplementation of 75 mg resveratrol resulted in a significant improvement in overall cognitive performance among middle-aged women. Foroumandi E et al [81] demonstrated promising positive effects on memory, quality of life, and levels of selective oxidative indices in patients with mild to moderate Alzheimer's disease (AD) who received 5 cc of fenugreek seed extract (equivalent to 500 mg of dry extract) (p < 0.001) for 4 months. The supplementation of 1000 mg/day of vitamin C [82], carotenoids: lutein and zeaxanthin (13 mg, or 27 mg/day) supplementation [83], as well as 1.6 g/day of alpha-lipoic acid [84] resulted in significant improvement compared to the control group in terms of attention, memory, and other observed cognitive tests (p < 0.05 for all).…”
Section: Results On Antioxidants and Cognitive Functionmentioning
confidence: 99%
“…In our current summary research, in a study by Thaung Zaw JJ et al [80], a daily supplementation of 75 mg resveratrol resulted in a significant improvement in overall cognitive performance among middle-aged women. Foroumandi E et al [81] demonstrated promising positive effects on memory, quality of life, and levels of selective oxidative indices in patients with mild to moderate Alzheimer's disease (AD) who received 5 cc of fenugreek seed extract (equivalent to 500 mg of dry extract) (p < 0.001) for 4 months. The supplementation of 1000 mg/day of vitamin C [82], carotenoids: lutein and zeaxanthin (13 mg, or 27 mg/day) supplementation [83], as well as 1.6 g/day of alpha-lipoic acid [84] resulted in significant improvement compared to the control group in terms of attention, memory, and other observed cognitive tests (p < 0.05 for all).…”
Section: Results On Antioxidants and Cognitive Functionmentioning
confidence: 99%
“…Given that pharmacology and nutrition have some points in common, we will also discuss some data we have found regarding the relationship between nutrition and AD. Various nutrients and nutraceuticals have been linked to improvements in cognition and other psychological aspects related to AD ( Guzman-Martinez et al, 2021 ; Abduljawad et al, 2022 ; Mahnashi et al, 2022 ; Xu Lou et al, 2023 ) Some examples include Gingko Biloba ( Liao et al, 2020 ), Melissa Officinalis ( Noguchi-Shinohara et al, 2020 ; Noguchi-Shinohara et al, 2022 ), Ginseng ( Ahmad et al, 2023 ), anti-inflammatory fatty acids ( Albrahim, 2020 ), medium-chain fatty acids ( Juby et al, 2022 ), ketone bodies ( Avgerinos et al, 2020a ), saffron ( Avgerinos et al, 2020b ; Talebi et al, 2021 ), fenugreek seed ( Foroumandi et al, 2023 ), genistein ( Viña et al, 2022 ), sodium oligomannate ( Xiao et al, 2021 ), anthocyanin ( Suresh et al, 2022 ), microbiota and probiotics ( Den et al, 2020 ; Maitre et al, 2021 ; Liu et al, 2022 ; Naomi et al, 2022 ), benfotiamine ( Gibson et al, 2020 ), omega-3 fatty acids ( Canhada et al, 2018 ; Jernerén et al, 2019 ), resveratrol ( Gu et al, 2021 ; Buglio et al, 2022 ; Fang et al, 2022 ; Tosatti et al, 2022 ), melatonin ( Tseng et al, 2022 ), citicoline ( Bonvicini et al, 2023 ), folic acid, vitamin B12 ( Chen et al, 2021 ), vitamins and minerals ( Mccleery et al, 2018 ; Karthika et al, 2022 ), selenium ( Pereira et al, 2022 ), vitamin D ( Jia et al, 2019 ), and mangosteen ( Muangpaisan et al, 2022 ). However, some studies do not support the efficacy of certain nutrients ( Zhu et al, 2018 ; Thancharoen et al, 2019 ; Araya-Quintanilla et al, 2020 ; Burckhardt et al, 2020 ; Du et al, 2020 ; Prabhakar et al, 2020 ; Shim et al, 2021 ; Tofiq et al, 2021 ; Takada et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the main causes of this phenomenon, oxidative stress, affects a number of metabolic pathways [40], and evidence of the involvement of free radicals in cognitive impairment has been obtained from patients suffering from neurodegeneration. In Alzheimer's disease, redox-mediated damage to various biomolecules has often been reported [41][42][43][44][45][46][47][48][49][50][51][52]. Thus, in the search for the mechanisms underlying this disorder, in addition to the dominant hypothesis of the amyloid cascade, an alternative explanation for the pathogenesis of this disease was proposed, which consisted of the relationship between mitochondrial dysfunction and the hyperproduction of reactive oxygen species.…”
Section: Free Radical Theory Of the Occurrence Of A Pathological Cond...mentioning
confidence: 99%